Orthographic Visualisation Induced Brain Activations in a Chronic Poststroke Global Aphasia with Dissociation between Oral and Written Expression - Jurgita Usinskiene; Michael Mouthon; Chrisovalandou Martins Gaytanidis; Agnes Toscanelli; Jean-Marie Annoni (Case Reports in Neurological Medicine)
We propose a method of orthographic visualisation strategy in a poststroke severe aphasia person with dissociation between oral and written expression. fMRI results suggest that such strategy may induce the engagement of alternative nonlanguage networks and visual representations may help improving oral output. This choice of rehabilitation method can be based on the remaining capacities and, therefore, on written language. Most notably, no study so far addressed how orthographic visualisation strategy during speech rehabilitation might influence clinical outcomes in nonfluent aphasia and apraxia patients.